2022
DOI: 10.1002/ese3.1063
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ca, Cr, Ga and Gd promotor over lanthana‐zirconia–supported Ni catalyst towards H2‐rich syngas production through dry reforming of methane

Abstract: Hydrogen production through methane dry reforming holds the promise of lowering greenhouse gases, that is CO2 and CH4, concentrations. Herein, Ca‐, Cr‐, Ga‐ and Gd‐promoted lanthana‐zirconia–supported Ni catalysts are investigated and characterized by X‐ray diffraction, Raman, infrared and UV‐vis spectroscopy, CH4‐temperature programmed surface reaction and cyclic reduction‐desorption experiment. All promoted catalyst systems had high and constant hydrogen yield (>70%) due to pronounced reoxidation capacity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…The peaks specified for monoclinic ZrO 2 were observed at 306, 345, 378, 534, 554, and 614 cm –1 , while the peak at 329 cm –1 was attributed to tetragonal ZrO 2 . The peaks at 473 and 634 cm –1 were assignable to both monoclinic and tetragonal ZrO 2 . These observations showed the presence of both phases, which is consistent with the results of XRD.…”
Section: Resultssupporting
confidence: 86%
“…The peaks specified for monoclinic ZrO 2 were observed at 306, 345, 378, 534, 554, and 614 cm –1 , while the peak at 329 cm –1 was attributed to tetragonal ZrO 2 . The peaks at 473 and 634 cm –1 were assignable to both monoclinic and tetragonal ZrO 2 . These observations showed the presence of both phases, which is consistent with the results of XRD.…”
Section: Resultssupporting
confidence: 86%
“…Among the different catalysts synthesized in this study, the 5Ni4Ba/YZr catalyst showed the highest hydrogen formation rate (1.14 mol g –1 h –1 ). On the basis of the results in Table S3 , it seems that the Ba promoter is a better choice than Ga, 94 Mn, 95 Al, 49 Al–Mn, 49 Pr, 44 Sm, 37 and Nd 44 promoters in terms of achieving a high hydrogen formation rate. At a ≤5 wt % Ni loading, a >0.9 H 2 /CO ratio, and a ≤0.1 g catalyst weight, Sc-, 20 La-, 41 Gd-, 48 and Ce 109 -promoted ordered mesoporous silica-supported Ni catalyst systems demonstrated a higher rate of H 2 formation than our catalyst system.…”
Section: Discussionmentioning
confidence: 99%
“…The catalytic activity of the above-discussed DRM catalysts and the other set of 54 DRM catalysts in terms of the H 2 yield, H 2 formation rate, and CO formation is shown in Table S3. The calculation details for hydrogen and CO formation rates are described in Supporting Information S2.…”
Section: Discussionmentioning
confidence: 99%
“…A chromium-promoted lanthana-zirconia-supported system stabilized the tetragonal ZrO 2 phase, stabilized the lanthana-zirconia phase, and showed excellent oxygen replenishment capacity as reduced NiO was re-oxidized by CO 2 up to the optimum level. It showed about 80% H 2 yield . The promotional addition of Ce over the tungsten-zirconia support also had a stable tetragonal zirconia phase .…”
Section: Introductionmentioning
confidence: 99%